Resettlers and survivors : Bukovina and the politics of belonging in West Germany and Israel, 1945-89 - Fisher, Gaëlle, 1985- (Berghahn, 2020)
"Located on the border of present-day Romania and Ukraine, the historical region of Bukovina was the site of widespread displacement and violence as it passed from Romanian to Soviet hands and back again during World War II. This study focuses on two groups of 'Bukovinians'--ethnic Germans and German-speaking Jews--as they navigated dramatically changed political and social circumstances in and after 1945. Through comparisons of the narratives and self-conceptions of these groups, Resettlers and Survivors gives a nuanced account of how they dealt with the difficult legacies of World War II, while exploring Bukovina's significance for them as both a geographical location and a 'place of memory.' "-- Provided by publisher.
Keywords: Jews -- Bukovina (Romania and Ukraine) -- History -- 20th century.; Jews, Romanian -- Israel -- History -- 20th century.; Jews, Ukrainian -- Israel -- History -- 20th century.; Germans -- Israel -- History -- 20th century.; Ukrainians -- Israel -- History -- 20th century.; Romanians -- Israel -- History -- 20th century.; Ukrainians -- Ethnic identity.; Romanians -- Ethnic identity.; Germans -- Ethnic identity.; Collective memory -- Bukovina (Romania and Ukraine); Bukovina (Romania and Ukraine) -- Ethnic relations -- History -- 20th century.; Bukovina (Romania and Ukraine) -- Emigration and immigration.; Juifs -- Bucovine (Roumanie et Ukraine) -- Histoire -- 20e siècle.; Allemands -- Israël -- Histoire -- 20e siècle.; Ukrainiens -- Israël -- Histoire -- 20e siècle.; Roumains -- Israël -- Histoire -- 20e siècle.; Ukrainiens -- Identité ethnique.; Roumains -- Identité ethnique.; Allemands -- Identité ethnique.; Mémoire collective -- Bucovine (Roumanie et Ukraine); Juifs roumains -- Israël -- Histoire -- 20e siècle.; HISTORY / Europe / Eastern; Collective memory; Emigration and immigration; Ethnic relations; Germans; Germans -- Ethnic identity; Jews; Jews, Romanian; Jews, Ukrainian; Romanians; Romanians -- Ethnic identity; Ukrainians; Ukrainians -- Ethnic identity; Europe -- Bukovina; Israel; 1900-1999; History